2015
DOI: 10.1007/s12281-015-0234-1
|View full text |Cite
|
Sign up to set email alerts
|

Majocchi’s Granuloma (Dermatophytic Granuloma): Updated Therapeutic Options

Abstract: Majocchi's granuloma (MG) is a rare, well-recognized, deep skin infection caused by dermatophyte, which can be seen in immunosuppressed as well as immunocompetent individuals. It is primarily caused by dermatophytes, most commonly Trichophyton rubrum; however, occasionally other Trichophyton sp., Trichosporon sp., Aspergillus sp., and Phoma sp. are involved. Diagnosis is based on clinical, mycological, and histological characteristics. This review focuses on clinical characteristics of MG and diagnosis and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 73 publications
1
9
0
10
Order By: Relevance
“…The most frequently observed pathogenic association was chronic use of high-potency topical corticosteroids in up to 64 % of cases, and previous studies reported this association in up to 50 % of cases [1,2,4]. The second associated factor was type 2 diabetes (16 %), and both factors were present in 56% of cases.…”
Section: Focus Dermatopathologymentioning
confidence: 83%
See 2 more Smart Citations
“…The most frequently observed pathogenic association was chronic use of high-potency topical corticosteroids in up to 64 % of cases, and previous studies reported this association in up to 50 % of cases [1,2,4]. The second associated factor was type 2 diabetes (16 %), and both factors were present in 56% of cases.…”
Section: Focus Dermatopathologymentioning
confidence: 83%
“…Granulomas with giant cells, lymphocytes, and histiocytes were seen, as were central necrosis, vasodilation and edema. Spores and hyphae were observed inside and outside hair follicles with the aid of periodic acid-Schiff (PAS) staining [2,4,5,9,12] (Figure 3).…”
Section: Focus Dermatopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Dermatophytische Granulome sind auch im Gesicht beschrieben worden (28 % der Fälle) [1] und wir beobachteten eine Gesichtsbeteiligung in 7 % unserer Fälle. Die wichtigsten Differenzialdiagnosen sind die Tinea corporis, die bakterielle Follikulitis und das Erythema nodosum [4] (Abbildungen 1, 2). Die histopathologische Analyse zeigte häufig eitrige Granulome (83 %).…”
unclassified
“…In den letzten Jahren wurde relativ häufig über dermatophytische Granulome berichtet, wahrscheinlich aufgrund einer erhöhten Inzidenz von prädisponierenden Faktoren (Typ-2-Diabetes mellitus, hämatologische Erkrankungen sowie die chronische Anwendung [topisch oder systemisch] von Glukokortikosteroiden) [3,5,6] Wir beobachteten eine hohe Rate von häufigen Dermatophytosen, hauptsächlich Onychomykosen; hyperglykämische Zustände können das Pilzwachstum und die zellvermittelte Immunantwort beeinflussen [4,14]. Weitere assoziierte Faktoren sind Lymphome (zum Beispiel Hodgkin-Lymphom) [1,4] und immunmodulatorische Medikamente wie TNFα-Inhibitoren [13]. Wir fanden heraus, dass 88,8 % der Patienten immunkompetent waren (einschließlich derer mit Grunderkrankungen wie Diabetes mellitus oder Glukokortikosteroidbehandlung); diese Zahl weicht von den Angaben in der Literatur (bis zu 60 %) ab [1,2].…”
unclassified